HOW TO IMPROVE PROBLEM SOLVING AND COMMUNICATION SKILLS OF PROSPECTIVE TEACHERS? A STUDY OF THE IMPACT OF RELIGIOUS INTEGRATION OF SCIENCE LEARNING - Winarto, Winarto; Sari, Maya Novita; Djainudin, Hamdhan; Rahayu, Dita Puji; Susbiyanto, Susbiyanto; Kristyaningrum, Dwi Hesty; Mustofa , Zaenal (LPPM Universitas Jambi, 2025)
The purpose of this study is to analyze the impact of integrated science learning on improving problem-solving and communication skills of prospective teachers. The research method is a non-equivalent group design experiment. This study involved 95 prospective teachers from three universities in Java. Communication data was measured using an observation sheet and problem-solving data was measured using a descriptive test instrument. The instrument has been assessed by experts in the field of science learning. The 21-item descriptive test instrument meets the assumption of the mean square MNSQ fit models in the range of 0.77-1.33. The data collection techniques used were tests and observations. The instruments used were problem-solving tests and observation sheets. The data analysis techniques used were independent t-tests. The results of this study showed differences in problem-solving skills and communication skills of students who used modules and those who did not. Based on the significance value, it is concluded that there is a difference between the control class and the experimental class based on significance value < 0.05. The achievement of prospective science teachers is good. The aspects of understanding, planning, and solving problems are good. However, the evaluation thinking aspect is not optimal. The communication achievement skills of seven aspects, namely messages, message forms, channels, noise, context, impact, and ethics are good. Meanwhile, the competency aspect is not optimal.